(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This paper presents an experimental study of the primary physical and mechanical properties of maize cobs (Zea mays L.) including mass, length, friction angle and temperature. Based on laboratory tests conducted on ten samples, the effects of moisture content and geometric parameters of the cobs on the uniformity and continuity of grain flow from hoppers are analysed. The findings are applicable to the design of hoppers and receiving devices in maize processing facilities.